The Characteristics of Meat Duck, Problems and Prevention of Off Flavor Due to Lipid Oxidation - Procula R Matitaputty; Suryana . (Indonesian Center for Animal Research and Development, 2010)
Source of poultry meat in Indonesia is currently dominated by chicken while local resources such as ducks have the potential to grow and be used as an alternative meat producer. Duck contribution towards the provision of a relatively small meat of 2.29%, compared with free-range chicken to reachs 20.33%. Sources of duck meat in Indonesia comes from local duck, and culled female ducks. Acceptance of most local duck meat is still relatively low, although in some areas local duck dishes are excellent. Meat ducks are generally less desirable, because taste and smell is different from chicken. Because consumers are not accustomed to the taste of typical meat, especially those that give the sensation of irregularities off meat – flavor or smell fishy/ rancid. Similarly, the color of duck meat is darker than that of chicken meat, high fat content of about 2.7 to 6.8%, which also influences consumer preferences. The high fat content, especially acid-unsaturated fatty acids in meat duck gives a tendency to produce off – flavors. Efforts to increase the consumption of duck meat should be based on the cause of the lack of acceptance by consumers. The smell of rancid meat duck is the most dominant cause of which is not liked by consumers. Efforts to reduce the off flavor of duck meat could be by adding antioxidant in feed stuffs. Key words: Duck meat, off-flavor, lipid oxidation, antioxidants